A rare enterouterine fistula between uterine leiomyoma and sigmoid colon in a nulliparous woman: a case report - M. Maivizhi Shruthi; Biswajit Sahoo; Saubhagya Kumar Jena; Pruthwiraj Sethi; Subarna Mitra; Manoj Kumar Nayak; Shilpy Jha; Nerbadyswari Deep Bag; Laveti Sai Sarvazna (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background The commonest benign neoplasm encountered in women of reproductive age group is uterine leiomyoma which usually presents with abnormal uterine bleeding, chronic pelvic pain, urinary disturbances, urinary retention, constipation, and dyspareunia. Uterine leiomyoma presenting with bowel fistulization is a rare presentation. To our knowledge and based on a thorough literature search, no previous reports of uterine leiomyoma showing spontaneous fistulous communication with the sigmoid colon have been reported. Case presentation A nulliparous woman in her early 30s presented with complaints of lower abdominal pain, abdominal fullness, pus discharge from the vagina, and difficulty in respiration. On contrast-enhanced computed tomography (CECT), a large heterogeneously enhancing mass was seen in the rectouterine space showing air-fluid levels, with a fistulous communication with the adjacent sigmoid colon. Histopathological examination proved the lesion to be a uterine leiomyoma. Conclusion The chance of fistulization with the bowel should be considered whenever a uterine mass with an air-fluid level is encountered.